Using power analysis to estimate appropriate sample size - Tomczak, Maciej; Tomczak, Ewa; Kleka, Paweł; Lew, Robert (Akademia Wychowania Fizycznego w Poznaniu)
The main aim of this paper is to provide some practical guidance to researchers on how statistical power analysis can be used to estimate sample size in empirical design. The paper describes the key assumptions underlying statistical power analysis and illustrates through several examples how to determine the appropriate sample size. The examples use hypotheses often tested in sport sciences and verified with popular statistical tests including the independent-samples t-test, one-way and two-way analysis of variance (ANOVA), correlation analysis, and regression analysis. Commonly used statistical packages allow researchers to determine appropriate sample size for hypothesis testing situations listed above
Keywords: power analysis; hypothesis testing; sample size estimation; sport science; examples